Alcohol Exposure May Increase Prenatal Choline Needs Through Redirection of Choline into Lipid Synthesis Rather than Methyl Donation - Hannah G. Petry; Nipun Saini; Susan M. Smith; Sandra M. Mooney (Metabolites)
Background: Prenatal alcohol exposure (PAE) can reduce fetal growth and cause neurodevelopmental disability. Prenatal choline supplements attenuate PAE-induced behavioral and growth deficits; however, the underlying mechanisms are unknown. Alcohol alters nutrient metabolism and potentially increases nutrient needs. Here, we investigate how alcohol affects choline metabolism in the maternal–fetal dyad and the role of supplemental choline. Methods: Pregnant C57BL/6J mice were assigned to one of four groups: alcohol-exposed (3 g/kg alcohol/day) or control +/− 100 mg/kg choline daily from embryonic day (E)8.5–17.5. We performed an exploratory hypothesis-generating analysis of targeted metabolomics on choline-related metabolites in the maternal liver, plasma, placenta, and fetal brain at E17.5 and Spearman correlation analyses to determine their association with gestational and fetal growth outcomes. Results: Although choline levels were largely unaffected by alcohol or choline, alcohol increased many lipid products in the CDP–choline pathway; this was not normalized by choline. Alcohol increased placental CDP–ethanolamine and reduced the maternal hepatic SAM/SAH ratio as well as dimethylglycine and the serine/glycine ratio across the dyad, suggesting a functional insufficiency in methyl donor pools. These outcomes were rescued by supplemental choline. Correlation analyses among choline metabolites and fetal growth outcomes suggest that maternal plasma methionine, serine, and the serine/glycine ratio may be predictive of maternal–fetal choline status. Conclusions: The increased hepatic lipid synthesis that characterizes chronic alcohol exposure may draw choline into phospholipid biosynthesis at the expense of its use as a methyl donor. We propose that PAE increases choline needs, and that its supplementation is necessary to fulfill these competing demands for lipid and methyl use.